Information Content In Accounting Profit And Economic - Dr. Dra. Ec. Elfreda Aplonia Lau, M.Si (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
Profit achievements has multy-meanings based on the interests ofstakeholders. The company's profit is the goal of a whole series ofactivities of the company, seen as the success of the owner, whoentrusts amount of capital for corporate leaders at various levels. Thecompany's profit was rated by owners as a chance to add an existingventure capital. Similarly, the company's profit is seen by owners as anopportunity to raise prive. In addition company's profit can be seen asthe success of the owner in prospering its employees. Investorsunderstand profit as a guarantee of return of invested funds, or theopportunity to increase investment in the company and enjoy thebenefits. Profit for investors as an indicator of progress or setbackseffort. Further, profit seen as the indicator of the progress and successof the businessfrom manager side. In terms of employees, profit broughthopes of enjoying an increase in salaries and wages and as theguaranty for the employee. The government respons to the profit as agreat hope of happiness of overcoming unemployment done by thecompanies. Besides the various profit mentioned, people needs thefulfillment of hygiene and health, water, soil and air.Profit is defined in two ways, namely economic profits as the maximumamount that is consumed during the period and at the end of the periodstill has the same wealth as at the beginning of the period. Meanwhile,the accounting profit is operationally defined as the difference betweenactual revenues arising from the period and historical costs to equal it.The information contained in accounting profit is understood as theengineering accounting, having information on historical cost, standardsetting and making up statements finance, long-termeconomicfeasibility, showing depreciation as cost allocation, unit of measure usedin the form of nominal rupiah and the basic concept use is continuitybussines. The information in economic profit intended for shareholders,short-term economic assessment, showing depreciation in economicvalue, unit of measure used is the purchasing power, and containsinformation that the basic concept used is liquidation or cash value.